Near-death experiences in non-life-threatening events and coma of different etiologies - Charland-Verville, Vanessa; Jourdan, Jean-Pierre; Thonnard, Marie; Ledoux, Didier; Donneau, Anne-Francoise; Quertemont, Etienne; Laureys, Steven (Frontiers in Human Neuroscience, 2014)
Background: Near death experiences (NDEs) are increasingly being reported as a clearly identifiable physiological and psychological reality of clinical significance. However, the definition and causes of the phenomenon as well as the identification of NDE experiencers is still a matter of debate. To date, the most widely used standardized tool to identify and characterize NDEs in research is the Greyson NDE Scale. Using this scale, retrospective and prospective studies have been trying to estimate their incidence in various populations but few studies have tackled to associate the experiences’ intensity and content related to etiology. Methods: This retrospective investigation assessed the most frequently recounted features of self-reported NDEs after a non-life-threatening event (i.e., “NDE-like” experience) or after a pathological coma (i.e., “classical NDEs”) and according to the etiology of the acute brain insult. We also compared our retrospectively acquired data in anoxic coma with historical data from the published literature on prospective post-anoxic studies using the Greyson NDE Scale. Results: From our 190 reports who met the criteria for NDE (i.e., NDE scale total score < 7/32), intensity (i.e., NDE scale total score) and content (i.e., NDE scale features) did not differ between “NDE-like” (n=50) and “real NDE” (n=140) groups, nor within the “real NDE” group depending on the cause of coma (anoxic/traumatic/other). The most frequently reported feature was peacefulness (89-93%). Only 2 patients (1%) recounted a negative experience. The overall NDE core features’ frequencies were higher in our retrospective anoxic cohort when compared to historical published prospective data. Conclusions: It appears that “real NDEs” after coma of different etiologies are similar to “NDE-like” experiences occurring after non-life threatening events. Subjects reporting NDEs retrospectively tend to have experienced a different content compared to the prospective experiencers